Differences in forest management practices in Primorsky Krai: Case study of certified and non-certified by Forest Stewardship Council forest concessions. (4th July 2019) - Nikolaeva, Alexandra Sasha; Kelly, Maggi; O'Hara, Kevin L.
ABSTRACT: The Forest Stewardship Council (FSC) aims to promote environmentally responsible forest management globally. However, quantifiable evidence of effects of FSC on forest management practices is lacking. FSC has been present in the Russian forestry arena for over 20 years. In this case study, we compare ecological indicators of forest management in FSC-certified and non-certified companies in Primorsky Krai of the Russian Far East. Those indicators include percent of forest cover loss and gain on forest concessions managed by three certified and three non-certified companies. We also interview a range of stakeholders involved with forest management or in forest policy planning in Russia to provide context for this case study. Results indicate no difference between certified and non-certified companies with regard to forest cover loss from 2008 to 2015 or forest cover gain from 2000 to 2012. Stakeholder interviews reveal that while forest certification is viewed positively and considered an efficient mechanism to improve forest management, the stakeholders doubt its ability to stimulate quantifiable changes in forest management practices in Russia and the Far East specifically. We focus on Primorsky Krai because of its unique geographic location, where its neighbors China and Japan significantly influence Primorsky Krai's export market.